2022
DOI: 10.1021/accountsmr.1c00280
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Structure Engineering for High-Performance Pb-Free Piezoceramics

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS:The increasing world energy crisis drives humans to harvest the energy in nature as much as possible without heavily damaging the environment. However, most of the energy in nature cannot be used directly. Therefore, pursuing technologies or matter that can directly interconvert different energies has been one of the most cutting-edge fields in science and technology. Such a magic ability exists in true-life piezoelectric materials that generate charge when bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 49 publications
(162 reference statements)
0
19
0
Order By: Relevance
“…By introducing local disorder and randomness, the phenomenon of deviations from the perfection occurring at the nanoscale, breaks the long-range correlation and average symmetry, providing enormous freedoms for modifying the properties of matter 2 . This strategy has been successfully established in perovskite relaxor ferroelectrics—complex oxides exhibiting the frequency-dependent diffusive phase transition that can substantially enhance dielectric and electromechanical properties 3 5 . Although these improved properties are often attributed to local (nanoscale) symmetry breaking, due to the lack of a clear understanding of their underlying structures, correlating the microscopic physical nature to material performance remains a decisive challenge in these “mess” systems (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing local disorder and randomness, the phenomenon of deviations from the perfection occurring at the nanoscale, breaks the long-range correlation and average symmetry, providing enormous freedoms for modifying the properties of matter 2 . This strategy has been successfully established in perovskite relaxor ferroelectrics—complex oxides exhibiting the frequency-dependent diffusive phase transition that can substantially enhance dielectric and electromechanical properties 3 5 . Although these improved properties are often attributed to local (nanoscale) symmetry breaking, due to the lack of a clear understanding of their underlying structures, correlating the microscopic physical nature to material performance remains a decisive challenge in these “mess” systems (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Growing environmental concerns over lead toxicity have driven the search for lead-free alternatives in recent years 5 , 10 . Inspired by the heterovalent B-site cations (Mg 2+ , Nb 5+ ) in the canonical relaxor system PbMg 1/3 Nb 2/3 O 3 (PMN), lead-free Bi 0.5 Na 0.5 TiO 3 (BNT)-based relaxor systems with heterovalent A-site cations (Bi 3+ , Na + ) are expected to achieve comparable electromechanical properties that have been reported in Pb-based counterparts 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For a few examples, piezoelectric coefficients ( d 33 ) of 525 and 650 ± 20 pC/N were successively achieved at the PPB composition in KNNS–BNKH and KNNS–BNKZ–Fe–AS systems, respectively, which are comparable to those of commercial PZT ceramics 16,17 . The excellent piezoelectric properties have been verified to originate from the flattening energy barrier induced by PPB, benefiting the polarization reversal 13,14,17 . In addition, controlling the crystal orientation has proven to be a more effective method to improve the piezoelectric and electromechanical coupling properties by advantageously utilizing the strong anisotropy of crystals.…”
Section: Introductionmentioning
confidence: 88%
“…Extensive research has shown that the polymorphic phase boundary (PPB) in KNN‐based ceramics is beneficial for enhancing the piezoelectric response. In the region of multiphase coexistence, the domain wall is easily oriented under an external electric field, and the samples exhibit excellent piezoelectric properties, analogs to the morphotropic phase boundary in PZT 12,13 . The PPB can be successfully constructed at approximately room temperature by elevating the phase transition temperature between the rhombohedral (R) and orthorhombic (O) phases, and simultaneously decreasing the phase transition temperature between the orthorhombic and tetragonal (T) phases.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Thus, suitable lead-free ferroelectric alternatives have been developed. [4][5][6][7] BaTi 2 O 5 (BT2) materials have gained increased research attention because of the analogical T C and promising ferroelectricity similar to PZT materials. [8] BT2 materials exhibit state-of-the-art relative dielectric constant and ferroelectricity along with the b-axis of the crystallography in a single crystal [9] ; however, they could not be easily prepared by a conventional process.…”
Section: Introductionmentioning
confidence: 99%